Vibrio cholerae FeoA, FeoB, and FeoC Interact To Form a Complex - Stevenson, Begoña (J Bacteriol, 2016)
Feo is the major ferrous iron transport system in prokaryotes. Despite having been discovered over 25 years ago and found to be widely distributed among bacteria, Feo is poorly understood, as its structure and mechanism of iron transport have not been determined. The feo operon in Vibrio cholerae is made up of three genes, encoding the FeoA, FeoB, and FeoC proteins, which are all required for Feo system function. FeoA and FeoC are both small cytoplasmic proteins, and their function remains unclear. FeoB, which is thought to function as a ferrous iron permease, is a large integral membrane protein made up of an N-terminal GTPase domain and a C-terminal membrane-spanning region. To date, structural studies of FeoB have been carried out using a truncated form of the protein encompassing only the N-terminal GTPase region. In this report, we show that full-length FeoB forms higher-order complexes when cross-linked in vivo in V. cholerae. Our analysis of these complexes revealed that FeoB can simultaneously associate with both FeoA and FeoC to form a large complex, an observation that has not been reported previously. We demonstrate that interactions between FeoB and FeoA, but not between FeoB and FeoC, are required for complex formation. Additionally, we identify amino acid residues in the GTPase region of FeoB that are required for function of the Feo system and for complex formation. These observations suggest that this large Feo complex may be the active form of Feo that is used for ferrous iron transport. IMPORTANCE The Feo system is the major route for ferrous iron transport in bacteria. In this work, the Vibrio cholerae Feo proteins, FeoA, FeoB, and FeoC, are shown to interact to form a large inner membrane complex in vivo. This is the first report showing an interaction among all three Feo proteins. It is also determined that FeoA, but not FeoC, is required for Feo complex assembly.